Resolvin D1 Attenuates Inflammation and Pelvic Pain Associated with EAP by Inhibiting Oxidative Stress and NLRP3 Inflammasome Activation via the Nrf2/HO-1 Pathway - Zhang J; Chen J; Jiang Q; Feng R; Zhao X; Li H; Yang C; Hua X (Dove Medical Press, 2023)
Jiong Zhang,1,2,* Juan Chen,3,* Qing Jiang,1,* Rui Feng,2 Xiaohu Zhao,2 Haolin Li,2 Cheng Yang,2 Xiaoliang Hua1 1Department of Urology, the Second Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Urology, the First Affiliated Hospital of Anhui Medical University, Hefei, People's Republic of China; 3The Ministry of Education Key Laboratory of Laboratory Medical Diagnostics, the College of Laboratory Medicine, Chongqing Medical University, Chongqing, 400016, People's Republic of China*These authors contributed equally to this workCorrespondence: Cheng Yang, Department of Urology, the First Affiliated Hospital of Anhui Medical University, No. 218 Jixi Road, Shushan District, Hefei, 230022, People's Republic of China, Tel +86 0551 6292 3440, Fax +86 551 6363 3742, Email chengyang_md@163.com Xiaoliang Hua, Department of Urology, the Second Affiliated Hospital of Chongqing Medical University, No. 74 Linjiang Road, Yuzhong District, Chongqing, 400010, People's Republic of China, Tel\Fax +86 023 6369 3222, Email hua_xiaoliang@cqmu.edu.cnBackground: Resolvin D1 (RvD1), a member of the specialized pro-resolving lipid mediators family, has a potent anti-inflammatory effect and alleviates tissue damage. The purpose of the current research was to study the effect of RvD1 on CP/CPPS and the underlying mechanisms using a mouse model of experimental autoimmune prostatitis (EAP) mice.Materials and Methods: The EAP mouse model was successfully established, and was used to test the therapeutic effect of RvD1. Hematoxylin-eosin staining and dihydroethidium staining were used to evaluate the histological changes and oxidative stress levels of prostate tissues. Chronic pelvic pain was assessed by applying von Frey filaments to the lower abdomen. The superoxide dismutase enzyme and malondialdehyde levels were detected using enzyme-linked immunosorbent assay (ELISA). The levels of inflammation-related cytokines, including IL-1β, IL-6, and TNF-α were detected by ELISA.Results: RvD1 treatment ameliorated prostatic inflammation and the pelvic pain of EAP mice. RvD1 treatment could inhibit activation of the NLRP3 inflammasome and oxidative stress. RvD1 treatment could activate Nrf2/HO-1 signaling in mice with EAP. Blockade of Nrf2/HO-1 signaling abolished the RvD1-mediated inhibition of oxidative stress, NLRP3 inflammasome activation and the anti-inflammatory effect of RvD1 in EAP.Conclusion: RvD1 treatment can reduce inflammatory cell infiltration in prostate tissue and attenuate pelvic pain associated with EAP by inhibiting oxidative stress and NLRP3 inflammasome activation via the Nrf2/HO-1 pathway. These results provide new insights that RvD1 has the potential as an effective agent in the treatment of EAP.Keywords: chronic prostatitis and chronic pelvic pain syndrome, CP/CPPS, resolvin D1, inflammation, NLRP3 inflammasome, oxidative stress